1. konferenca Celovito zagotavljanje varnosti v organizacijah: Varnost in zdravstvene institucije, zbornik povzetkov (University of Maribor Press, 2024)
The 1st Conference Comprehensive Security Assurance in Organizations: Safety and Health Institutions, Book of Abstracts. The conference’s aim is to highlight the importance of comprehensive security provision in healthcare institutions. The central themes of the conference are security in healthcare institutions, including corporate security activities, and the significance of the "One Health" concept for ensuring public health quality. Ensuring the safety of employees in healthcare institutions is a prerequisite for the safe and high-quality treatment of patients. Corporate security plays a crucial role in this, tailored to the organisation and its field, and is based on quality management of security risks and threats in healthcare institutions. The One Health concept significantly complements the approaches to ensuring security in healthcare institutions. One Health is an inclusive and multisectoral approach that operates at local, regional, national, and global levels with the goal of achieving optimal health outcomes. It emphasises the interconnectedness between humans, animals, plants, and their shared environment.